2022
DOI: 10.1088/1748-9326/ac7b39
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable irrigation technologies: a water-energy-food (WEF) nexus perspective towards achieving more crop per drop per joule per hectare

Abstract: Sustainable agricultural intensification requires irrigation methods and strategies to minimise yield penalties while optimising water, land and energy use efficiencies. We assessed, from a silo-based and integrated water-energy-food (WEF) nexus perspective, the performance of irrigation technologies in different agro-climatic regions. Secondary to this, we assessed the impact of adopting systematic approaches such as the WEF nexus on improving efficiency in irrigated agriculture through irrigation modernizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…For example, a need exists to systematically appraise irrigation technologies and assess their performance at the field, farm and irrigation command scales, not just from a water perspective, but including energy, environment and economic considerations to inform sustainable transitions. For example, a study by Taguta, Dirwai, et al (2022) used an integrated WEF nexus approach to assess the potential benefits of transitioning among furrow, sprinkler and trickle irrigation technologies in different agro‐climatic zones. The results showed that shifting from flood irrigation to sprinkler and drip systems improved water productivity (WP).…”
Section: The Future Of Awm Across Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a need exists to systematically appraise irrigation technologies and assess their performance at the field, farm and irrigation command scales, not just from a water perspective, but including energy, environment and economic considerations to inform sustainable transitions. For example, a study by Taguta, Dirwai, et al (2022) used an integrated WEF nexus approach to assess the potential benefits of transitioning among furrow, sprinkler and trickle irrigation technologies in different agro‐climatic zones. The results showed that shifting from flood irrigation to sprinkler and drip systems improved water productivity (WP).…”
Section: The Future Of Awm Across Scalesmentioning
confidence: 99%
“…Approaches to AWM research and innovation have traditionally been water-centric and focused at the field and scheme scales (Scheierling et al, 2014(Scheierling et al, , 2016Scheierling & Treguer, 2018;Taguta, Dirwai, et al, 2022). While this proved essential for producing 'more crop per drop' at a local scale, there is potential for trade-offs at larger scales such as landscapes and river basins due to the efficiency paradox (Grafton et al, 2018) or the rebound effect as farmers are tempted to expand their area or by switching to high-value water-intensive crops using the saved water (Hamidov, Kasymov, et al, 2022).…”
Section: Nexus Approaches For Thinking Beyond Water In Awmmentioning
confidence: 99%
See 1 more Smart Citation
“…The second constraint is the challenges around agricultural water management including issues like year-round availability of irrigation water, irrigation technologies, technical support to farmers, fertilizer, and seeds [ [16] , [21] , [22] ]. In Nepal, during the dry season, the mid and tail sections of the canal system experience water shortage particularly within the surface irrigation network.…”
Section: Introductionmentioning
confidence: 99%
“…Under this framework, it is reasonable to think that a possible way to increase rice production could be to increase the area devoted to paddy rice linked to increasing the irrigated land. Nevertheless, new irrigation developments must align with the current metanarratives, such as the sustainability principles, the ecosystem services and the nexus of water-food-marketenergy-security (Fonteh, 2017;Ofosu et al, 2014;Taguta et al, 2022). With this in mind, sustainable water management should be promoted, to enhance the multifunctional roles of paddy rice (food and straw provision, flood control, biodiversity, etc.).…”
Section: Introductionmentioning
confidence: 99%